Farmers' Behavior to Increase Innovation Capacity in The Special Region of Yogyakarta Within Framework of Agricultural Innovation System - Mustapit, Mustapit; Hariadi , Sunarru Samsi; Santosa, Krishna Agung (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2025)
Agricultural innovation is needed to increase agricultural productivity. The Special Region of Yogyakarta is a farming area that needs to increase its farmers' capacity to innovate because, for the last 2 years, rice productivity has decreased and is below the national average rice productivity. This study aims to analyze the influence of farmers' personal factors (attitude towards innovation, self-efficacy, and motivation) and agricultural environmental factors (the role of farmer groups, the role of agricultural extension workers, the role of input and crop traders, the role of research institutions and the role of the government) on farmers' behavior to increase the capacity to innovate within framework of the agricultural innovation system. This research is survey research with a quantitative method approach. The data analysis method was conducted with structural equation modeling (SEM) analysis. The analysis results show that personal factors have no significant effect in shaping the behavior of The Special Region of Yogyakarta farmers in increasing the innovation capacity in agriculture. Farmers' attitudes towards innovation in low rice commodities, negative self-efficacy, and motivation have no effect in shaping farmers' behavior in increasing the capacity to innovate in agriculture. Environmental factors significantly influence farmers' behavior in increasing the capacity to innovate in agriculture. The role of farmer groups, agricultural extension workers, traders, research institutions, and the government will influence the behavior of farmers in improving innovative, adaptive, and absorptive capacity. There is no relationship between personal factors and environmental factors, with a low correlation coefficient.